ODAP levels in some Lathyrus species distributed on Burdur-Isparta provinces in Turkey - Karadeniz, Asuman; Erdogan, Neslihan; Genc, Hasan; Emre, Irfan (Springer, 2010)
Lathyrus species are distributed in natural areas of Turkey and are cultivated for use in human and animal food. Plants and seeds of Lathyrus species contain a neurotoxic substance called beta-N-oxalyl-L-alpha, beta-diamino propanoic acid (ODAP). When consumed in large quantities, ODAP may cause a kind of paralysis known as lathyrism. In this note, ODAP levels were determined in Lathyrus species collected in the Burdur-Isparta provinces. The leaves and seeds of plant samples were analysed using High Performance Liquid Chromatography (HPLC). ODAP was not detected in L. aphaca L. var. pseudoaphaca (Boiss.) Davis, L. sphaericus Retz., or L. aureus (Stev.) Brandza; the seed samples of L. cicera L. and L. clymenum L. contained 0.053 and 0.171% ODAP, respectively. Leaf samples of L. cicera L. contained 0.018% ODAP. This preliminary note seems to point to a secondary gene pool that may serve as a valuable source of genetic material for grass pea improvement.
Keywords: ODAP; Lathyrus spp.; HPLC; Turkey